Minimally invasive surgery in older children with Hirschsprung’s disease in a North African Country - Ahmed Arafa; Ahmed Arafa; Moutaz Ragab; Moutaz Ragab; Osama Abdelazim; Osama Abdelazim; Sayed Khedr; Sayed Khedr; Wesam Mohamed; Wesam Mohamed (Frontiers in Surgery, 2022)
IntroductionHirschsprung's disease (HSD) is a bowel congenital anomaly affecting mainly the enteric nervous system of the rectosigmoid region. Surgical resection of the aganglionic segment and restoration of bowel continuity via coloanal anastomosis is the main stay of treatment. In 1999, Georgeson et al. introduced a new minimally invasive approach as a standard for the pull-through mechanism. This study aims to evaluate the safety and possibility of the use of a laparoscope in older children with HSD with various techniques for HSD surgery.MethodsThis study was performed based on 20 patients diagnosed with HSD. The patients are older children, whose mean age is 3 years. The cases showing enterocolitis or obstruction were excluded from the study. We divided these cases into two groups: Group A, consisting of 10 cases where laparoscopic-aided transanal pull-through was done, and group B, in which the laparoscopic Duhamel procedure was done.ResultsWe compared between two groups for the first year follow-up period. In Group A, there were two cases of stenosis that respond to regular dilation: one case of enterocolitis and one case of fecal incontinence. In Group B, we had two cases of constipation and three cases of enterocolitis. There was no anastomotic leak in both groups.ConclusionMinimally invasive surgery is safe in management of HSD in older children in one stage, either by using the Duhamel or transanal Swenson procedure.